A compact skeletal mechanism for n-dodecane with optimized semi-global low-temperature chemistry for diesel engine simulations. (1st March 2017) - Yao, Tong; Pei, Yuanjiang; Zhong, Bei-Jing; Som, Sibendu; Lu, Tianfeng; Luo, Kai Hong
Abstract: A skeletal mechanism with 54 species and 269 reactions was developed to predict pyrolysis and oxidation of n -dodecane as a diesel fuel surrogate involving both high-temperature (high-T) and low-temperature (low-T) conditions. The skeletal mechanism was developed from a semi-detailed mechanism developed at the University of Southern California (USC). Species and reactions for high-T pyrolysis and oxidation of C5 -C12 were reduced by using reaction flow analysis (RFA), isomer lumping, and then merged into a skeletal C0 -C4 core to form a high-T sub-mechanism. Species and lumped semi-global reactions for low-T chemistry were then added to the high-T sub-mechanism and a 54-species skeletal mechanism is obtained. The rate parameters of the low-T reactions were tuned against a detailed mechanism by the Lawrence Livermore National Laboratory (LLNL), as well as the Spray A flame experimental data, to improve the prediction of ignition delay at low-T conditions, while the high-T chemistry remained unchanged. The skeletal mechanism was validated for auto-ignition, perfectly stirred reactors (PSR), flow reactors and laminar premixed flames over a wide range of flame conditions. The skeletal mechanism was then employed to simulate three-dimensional turbulent spray flames at compression ignition engine conditions and validated against experimental data from the Engine Combustion Network (ECN).